Employee Perceptions of Their Organization's Level of Emergency Preparedness Following a Brief Workplace Emergency Planning Educational Presentation - Lauren A. Renschler; Elizabeth A. Terrigino; Sabiya Azim; Elsa Snider; Darson L. Rhodes; Carol C. Cox (Elsevier, 2016)
A brief emergency planning educational presentation was taught during work hours to a convenience sample of employees of various workplaces in Northern Missouri, USA. Participants were familiarized with details about how an emergency plan is prepared by management and implemented by management-employee crisis management teams - focusing on both employee and management roles. They then applied the presentation information to assess their own organization's emergency preparedness level. Participants possessed significantly (p < 0.05) higher perceptions of their organization's level of emergency preparedness than non-participants. It is recommended that an assessment of organizational preparedness level supplement emergency planning educational presentations in order to immediately apply the material covered and encourage employees to become more involved in their organization's emergency planning and response. Educational strategies that involve management-employee collaboration in activities tailored to each workplace's operations and risk level for emergencies should be implemented.